Selective Neuron Vulnerability in Common and Rare Diseases—Mitochondria in the Focus - Paß, Thomas; Wiesner, Rudolf J.; Pla-Martín, David (Frontiers in Molecular Biosciences, 2021)
Mitochondrial dysfunction is a central feature of neurodegeneration within the central and peripheral nervous system, highlighting a strong dependence on proper mitochondrial function of neurons with especially high energy consumptions. The fitness of mitochondria critically depends on preservation of distinct processes, including the maintenance of their own genome, mitochondrial dynamics, quality control, and Ca2+ handling. These processes appear to be differently affected in common neurodegenerative diseases, such as Alzheimer’s and Parkinson’s disease, as well as in rare neurological disorders, including Huntington’s disease, Amyotrophic Lateral Sclerosis and peripheral neuropathies. Strikingly, particular neuron populations of different morphology and function perish in these diseases, suggesting that cell-type specific factors contribute to the vulnerability to distinct mitochondrial defects. Here we review the disruption of mitochondrial processes in common as well as rare neurological disorders and its impact on selective neurodegeneration. Understanding discrepancies and commonalities regarding mitochondrial dysfunction as well as individual neuronal demands will help to design new targets and to make use of already established treatments in order to improve treatment of these diseases.